Clichés orientalistes et stéréotypes formels dans un roman satirique : le cas de La vieille dame du riad de Fouad Laroui - Zdrada-Cok, Magdalena (Romanica Silesiana, 2021)
This article analyses the novel “La vieille dame du riad” (2011) by Fouad Laroui, a Moroccan-Dutch writer of French expression. We examine the strategies (generic and intertextual) used by the novelist to ridicule the Orientalist prejudices which persist in the current time. Generic hybridity (the presence of some elements of the detective story, fantasy novel and oriental tale) is used to develop the satirical dimension of the novel.